Chicken γδ T cells proliferate upon IL-2 and IL-12 treatment and show a restricted receptor repertoire in cell culture - Linti, Antonia E.; Göbel, Thomas W.; Früh, Simon P. (Frontiers in Immunology, 2024)
In the chicken, γδ T cells represent a large fraction of peripheral T cells, however, their function is still largely unknown. Here, we describe the selective in vitro expansion of γδ T cells from total splenocytes by stimulation with cytokines IL-2 and IL-12. Under these conditions γδ T cells proliferated preferentially and reached frequencies of more than 95% within three weeks. While IL-2 alone also triggered proliferation, an increased proliferation rate was observed in combination with IL-12. Most of the expanded cells were γδ TCR and CD8 double positive. Splenocytes sorted into TCR1+CD8+, TCR1highCD8- and TCR1lowCD8- subsets all proliferated well upon dual stimulation with IL-2/IL-12, indicating that all three γδ T cell subsets do not require bystander activation for proliferation. TCR1+CD8+ cells maintained CD8 surface expression during stimulation, while CD8- subpopulations showed varied levels of CD8 upregulation, with the highest upregulation observed in the TCR1high subset. Changes in the γδ T cell receptor repertoire during cell culture from day 0 to day 21 were analyzed by next generation sequencing of the γδ variable regions. Overall, long-term culture led to a restricted γ and δ chain repertoire, characterized by a reduced number of unique variable region clonotypes, and specific V genes were enriched at day 21. At day 0, the δ chain repertoire was highly diverse and the predominant clonotypes differed between animals, while the most frequent γ chain clonotypes were shared between animals. On day 21 however, the most frequent clonotypes in both γ and δ chain repertoires were different between animals, indicating that selective expansion of dominant clonotypes during stimulation seems to be an individual outcome. In conclusion, IL-2 and IL-12 are sufficient to stimulate in vitro outgrowth of γδ T cells. The analyses of the TCR repertoire indicate that the culture leads to an expansion of individual T cell clones, which may reflect a previous in vivo activation. This system will be instrumental to study γδ T cell function.